2007
DOI: 10.1007/s00436-006-0425-3
|View full text |Cite
|
Sign up to set email alerts
|

Reinfections and Trypanosoma cruzi strains can determine the prognosis of the chronic chagasic cardiopathy in mice

Abstract: Chronic Chagas' disease represents the result of the interaction between the host and the parasite, producing different clinical features: from a mild disease to a severe heart failure. In the present investigation, we analyzed whether Trypanosoma cruzi strain and/or reinfections in the acute stage, determine changes in the chronic phase (135 days postinfection, d.p.i) that could explain the diverse evolution of cardiac lesions. After infection of albino Swiss mice (n = 170) with 50 blood trypomastigote of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 8 publications
1
28
0
4
Order By: Relevance
“…Many experts also believe that intense exposure to infected vectors and repeated T. cruzi reinfection contributed to accelerated progression of cardiomyopathy and high rates of severe disease in the decades before the Southern Cone Initiative began in 1991, and that vector control has led to an amelioration of Chagas cardiomyopathy since then [32], [33], [34]. Although this hypothesis is difficult to test in human populations, animal models provide supporting evidence that repeated infection worsens the long-term prognosis of Chagas heart disease [35]. We observed that patients who had lived in a house with earthen floor and walls were more likely to have severe Chagas cardiomyopathy; this finding may reflect poor housing conditions acting as a proxy for more intense vector exposure and reinfection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Many experts also believe that intense exposure to infected vectors and repeated T. cruzi reinfection contributed to accelerated progression of cardiomyopathy and high rates of severe disease in the decades before the Southern Cone Initiative began in 1991, and that vector control has led to an amelioration of Chagas cardiomyopathy since then [32], [33], [34]. Although this hypothesis is difficult to test in human populations, animal models provide supporting evidence that repeated infection worsens the long-term prognosis of Chagas heart disease [35]. We observed that patients who had lived in a house with earthen floor and walls were more likely to have severe Chagas cardiomyopathy; this finding may reflect poor housing conditions acting as a proxy for more intense vector exposure and reinfection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite load, time of infection and exposure to reinfection are extremely hard to ascertain while studying human populations. Using animal models, it has been possible to demonstrate that these factors affect protection and pathology following T. cruzi infection [12][13][14]. It has been shown, in experimental as well as human T. cruzi infection, that parasites isolated from different organs are genetically distinct, suggesting that the genetic variability of the parasite strains may influence disease outcome [15,16].…”
Section: Theories For the Generation And Maintenance Of (Immuno) Pathmentioning
confidence: 99%
“…It has been repeatedly proposed that infected people living in endemic areas suffer from frequent reinfections, and that such reinfections increase the strength of cardiomyopathy in humans [28, 29, 32], just as they do in mice [2022, 30, 31]. Although those epidemiological studies were based on sound statistical comparisons between individuals with different levels of exposure to vectors, none of them provided estimates of the actual level of vector-human contacts and its associated number of reinfection events per person.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors proposed a role of reinfections in pathogeny. Although parasitaemia is lower in the reinfections compared to the primary infection in animal models [20, 22, 23], reinfections may aggravate chronic disease in mice [2022, 30, 31] and they may be associated to chronic cardiac damage in humans [28, 29, 32]. To determine the frequency of reinfections and the ability of the human immune system to prevent them is thus essential to our understanding of the disease dynamics.…”
Section: Introductionmentioning
confidence: 99%